Combinatorial screening of osteoblast response to 3D calcium phosphate/poly(ε-caprolactone) scaffolds using gradients and arrays - Chatterjee, Kaushik; Sun, Limin; Chow, Laurence C.; Young, Marian F.; Simon, Carl G. (Biomaterials, 2011)
There is a need for combinatorial and high-throughput methods for screening cell–biomaterial interactions to maximize tissue generation in scaffolds. Current methods employ a flat two-dimensional (2D) format even though three-dimensional (3D) scaffolds are more representative of the tissue environment in vivo and cells are responsive to topographical differences of 2D substrates and 3D scaffolds. Thus, combinatorial libraries of 3D porous scaffolds were developed and used to screen the effect of nano-amorphous calcium phosphate (nACP) particles on osteoblast response. Increasing nACP content in poly(ε-caprolactone) (PCL) scaffolds promoted osteoblast adhesion and proliferation. The nACP-containing scaffolds released calcium and phosphate ions which are known to activate osteoblast function. Scaffold libraries were fabricated in two formats, gradients and arrays, and the magnitude of the effect of nACP on osteoblast proliferation was greater for arrays than gradients. The enhanced response in arrays can be explained by differences in cell culture designs, diffusional effects and differences in the ratio of “scaffold mass to culture medium”. These results introduce a gradient library approach for screening large pore 3D scaffolds and demonstrate that inclusion of the nACP particles enhances osteoblast proliferation in 3D scaffolds. Further, comparison of gradients and arrays suggests that gradients were more sensitive for detecting effects of scaffold composition on cell adhesion (short time points, 1 day) whereas arrays were more sensitive at detecting effects on cell proliferation (longer time points, 14 day).